Fatigue crack initiation in powder metallurgically-processed tool steel material under cyclic loading / Al Emran Ismail and Mohd Nor Berhan - Ismail, Al Emran; Berhan, Mohd Nor (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2006)
The cyclic behavior of P/M steel has been evaluated at different tempering conditions. Heat treatment is found to significantly affect the hardness, micro structure and fatigue response of the material. Optimum tempering temperature is found to give the highest hardness and better fatigue life compare to as-received material. This heat treatment also characterizes the mechanisms of fatigue crack initiations. Three mechanisms are found in this material: (I) crack initiated from broken particle, (2) crack initiated from open pore and (3) crack initiated from interfacial debonding between particle and matrix. It has been observed that, by carefully designing the heat treatment this steel can be beneficially used in fatigue loaded components.